A dual-phase biologic augmentation of rotator cuff healing in a preclinical rat model using interleukin-17F and low-dose lithium - Manisha R. Mistry, MD, MSc; Yufa Wang, MD, MSc; Cari M. Whyne, PhD; David M. Phillips, MSc; Wendy Oakden, PhD; Paul Marks, MD; Jimmy Tat, MD, MSc; Diane Nam, MD, MSc (JSES International)
Background: Rotator cuff tendon tears are a common cause of shoulder dysfunction in adults. Yet, impaired healing continues to result in higher failure rates after surgical repair resulting in patient dysfunction and prolonged recovery. This has spurred increased investigation of biologic augmentation to improve tendon healing. This study examines the outcome of peritendinous interleukin-17F (IL-17F) administration and oral low-dose lithium carbonate (Li) on rotator cuff healing following acute surgical repair in a rat model. Methods: Treatment group included an open supraspinatus peel and repair followed by a local injection of IL-17F at the bone–tendon interface and a 7-day course of oral Li. Control rats received no additional intervention before surgical closure. Evaluation of healing was then preformed using MRI imaging, biomechanical testing, and histological analysis at the bone–tendon interface. Results: Eighteen rats (9 control, 9 experimental) underwent complete testing. Combined treatment of peritendinous IL-17F and oral low-dose Li after rotator cuff repair improved rotator cuff healing in all outcomes when compared to controls. MRI imaging in the treatment group showed complete healing of all supraspinatus tendons across the anatomic footprint after repair. We also found significant increases in biomechanical stiffness compared to controls (P < .01). At the histological level, treatment groups also had decreased osteoclasts (P < .001), and increased histologic organization of fibroblasts compared to controls. These findings are consistent with an increase in biomechanical stiffness. Conclusion: We demonstrated that the combined treatment of IL-17F and oral low-dose lithium improved rotator cuff tendon healing quality following acute surgical repair in a rat model.